Characteristics of Patients of Descending Necrotizing Mediastinitis Thoracic, Cardiac and Vascular Surgery Subsection Thoracic in Dr. Mohammad Hoesin General Hospital From 1 November 2019 to 30 November 2020 - Arisma Putra; Gama Satria; Bermansyah; Ahmat Umar; Aswin Nugraha (Sriwijaya Journal of Surgery, 2021)
Background: Acute mediastinitis is an infection of the connective tissue of the interpleural mediastinal space. The infection may spread through the cervical spaces to the mediastinum, via negative intrathoracic pressure and gravity.1 Management of DNM with minimally invasive drainage, namely video-assisted thoracic surgical drainage (VATS),6 mediastinoscopy,7 and percutaneous catheter drainage,8,9 have been widely used. During early 1920s, data showed subsequent to broad-spectrum antibiotics, the mortality rate was about 40%.12 Furthermore, without prompt diagnosis and aggressive surgery, the mortality rate can reach up to 60%.13 Methods: This retrospective study has a descriptive research design. The number of samples is 19 subjects. Results: From January 1, 2019 to November 30, 2020 there were 19 DNM patients. In this study, most DNM patients were male, average age of 39 years, dental abscesses as the most common source of infection, neck exploration and sternotomy were the most common treatment option, most common outcome death, and the most common result of culture was Acinetobacter baumannii. Conclusion: Good non-operative and operative management can reduce mortality rate.